Efeito da (+)-catequina sobre adiscinesia orofacial induzida por reserpina em camundongos e atividade damonoaminoxidase - Reinheimer, Jeane Binotto (2018)
Tardive dyskinesia (TD) is a disabling and debilitating disorder due to the chronic use of antipsychotics that affects around 20% to 50% of patients. It is characterized by involuntary, repetitive and abnormal movements that mainly involve the musculature of the oro-tongue-facial region. There are several hypotheses that attempt to explain its pathophysiological mechanism, but none is fully elucidated. There is evidence that oxidative stress produced throughout the metabolism of dopamine by monoaminoxidase (MAO) is associated with the manifestation of this extrapyramidal adverse effect. In the United States, Valbenazine and Deutetrabenazine have been approved by the Food and Drug Administration for the treatment of TD, but these drugs can cause serious adverse effects, such as cardiac arrhythmia. In Brazil, there is no totally efficient treatment to minimize these involuntary movements. A (+)-catechin is a polyphenolic compound with antioxidant properties and has promising neuroprotective activity. Therefore, the objective of this study was to evaluate the effect of (+)-catechin on orofacial dyskinesia induced by reserpine in mice and the possible involvement of the MAO enzyme. In vitro, (+)-catechin inhibited the activity of the two MAO isoforms at concentrations of 0.34 and 1.03 mM reversibly for MAO-A and partially reversible for MAO-B. To evaluate the effects of (+)-catechin on reserpine-induced OD, male Swiss mice (weighing 25-35 g) were treated daily for 4 days with reserpine (1 mg/kg, s.c.) or vehicle. Then (+)-catechin (10, 50 or 100 mg/kg, i.p.) or its vehicle was administered for another 20 days. On days 6, 8, 15 and 26 of the experimental period, vacuous chewing movements (VCMs) and locomotor and exploratory activities were quantified. Reserpine increased VCMs and decreased locomotor and exploratory activities. A (+)-catechin decreased the number of VCMs only after the second administration of the 10 mg/kg dose on the 6th day of the experimental period in the pre-treated group with reserpine without changing any other behavioral parameter. The other doses tested did not modify any behavioral parameters. No alteration was observed in MAO activity in the striatum and substantia nigra of mice treated with reserpine or (+)-catechin. Therefore, further studies should be performed to clarify the potential neuroprotection of (+)-catechin and its impact as pharmacological therapy, aiming to increase the quality of life of patients with TD.